Developing a theoretical model Of agriculture takaful for paddy farmers in east coast Malaysia - Nurul Ashykin Abd Aziz; Mohammad Ismail; Nurul Aien Abd. Aziz; Noreen Noor Abd Aziz (2014)
The agriculture industry is one of the sectors most susceptible to climate change. Variations in climate, ranging from erratic rainfalls, prolonged dry spells and extremes in temperature may affect the agriculture community in terms of price and production. Insects and diseases stemming from weather related conditions can also impact both quality and yield of a crop. The effects of these weather risks can be broadly summarized into two; namely price and production risks. Price risks are risks associated with fluctuations in the market price of the agriculture commodities; whilst production risks encompass variations in the output and quality of the agriculture commodities. In recent years, natural disasters have wrecked havoc and devastation worldwide. Since climatic change is inevitable, developing countries whose economies are highly dependent on agriculture, have devised innovative strategies to increase yields and crops resistant to climatic risks, same goes to Malaysia. In accordance, Malaysian government has been introduced insurance to the agriculture sector known as Paddy Takaful Scheme Insurance that focused to the paddy farmers in the Budget 2013. Therefore the needs of the target market should be defined properly to enable the insurance providers as well as the government to develop sound strategies. Their opinions, perceptions and attitudes towards this insurance scheme product have to be gathered and interpreted. Understanding the perceptions of the target market and aligning it with the proposed insurance model are essential in determining the success and acceptance of crop insurance among the paddy farmers.